Finer linkage mapping of primary hip osteoarthritis susceptibility on chromosome 11q in a cohort of affected female sibling pairs. - Chapman, K; Mustafa, Z; Dowling, B; Southam, L; Carr, A; Loughlin, J (2002)
OBJECTIVE: To finer linkage-map a primary osteoarthritis (OA) susceptibility locus as a prerequisite to linkage disequilibrium/association analysis. METHODS: A 50-cM interval of chromosome 11q that we had previously identified as harboring susceptibility to hip OA in a female sibling-pair cohort was subjected to finer linkage mapping. Thirty-five microsatellite markers with a mean marker interval of 1.4 cM were genotyped in 146 families containing female sibling pairs who were concordant for hip OA, as ascertained by total hip replacement. RESULTS: Two-point and multipoint linkage analysis revealed 2 distinct regions of linkage within the 50-cM interval. The first locus had a linkage interval of 11.9 cM and was centered at 81.5 cM from the 11p telomere, with a maximum multipoint logarithm of odds (LOD) score of 2.4. The second region had a linkage interval of 6.5 cM and was centered at 93.1 cM from the 11p telomere, with a maximum multipoint LOD score of 1.8. CONCLUSION: Dense linkage mapping has highlighted the presence of 2 loci on chromosome 11q, each conferring susceptibility to hip OA. Both loci are sufficiently narrow for association analysis to be undertaken.